IMPLEMANTASI INOVASI SEBAGAI BAGIAN NILAI ORGANISASI BADAN NARKOTIKA NASIONAL DAERAH ISTIMEWA YOGYAKARTA - Wahyu Rahmawati; Aftoni Susanto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The issue of drug abuse or drug use is still a problem that is quite concerning for the Indonesian people now. Indonesia is the right target for drug traffickers because of its large population and a large number of young people. It is a big challenge for the government to overcome this problem, through institutions, namely the National Narcotics Agency. The pattern of prevention and eradication that is secured and the illicit traffic of narcotics cannot be carried out in the old ways and in the same way. Innovation or new ways are needed to improve the performance of the National Narcotics Agency. One of the organizational values ​​of the National Narcotics Agency is innovatif. This study aims to explore the implementation of innovation in the National Narcotics Agency, for the Special Region of Yogyakarta (BNNP DIY). The research was conducted using a descriptive qualitative method. The results of the research prove that there is an implementation of innovation at BNNP DIY through new programs, new methods, and improving service quality. The innovation aims to optimize the implementation of the function of preventing and eradicating the threat and circulation of illicit drugs in Yogyakarta.